2018
DOI: 10.1017/s0033291718001757
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and well-being trends among children and young people in the UK, 1995–2014: analysis of repeated cross-sectional national health surveys

Abstract: Despite a striking increase in the reported prevalence of long-standing mental health conditions among UK CYP, there was relatively little change in questionnaire scores reflecting psychological distress and emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
117
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 19 publications
12
117
1
1
Order By: Relevance
“…Of the mental disorders studied, lifetime mood (MDD and bipolar disorder) and anxiety (GAD and OCD) disorders showed significant associations with PMH even after controlling for important confounders such as history of chronic physical illnesses. These findings were expected given the preliminary studies in Singapore and the UK that have found association of PMH and mental well-being with either diagnosed mental disorders or symptoms of depression and anxiety [26,36]. However, this is the first study that assessed PMH among individuals meeting DSM-IV criteria for AUD.…”
Section: Discussionmentioning
confidence: 58%
“…Of the mental disorders studied, lifetime mood (MDD and bipolar disorder) and anxiety (GAD and OCD) disorders showed significant associations with PMH even after controlling for important confounders such as history of chronic physical illnesses. These findings were expected given the preliminary studies in Singapore and the UK that have found association of PMH and mental well-being with either diagnosed mental disorders or symptoms of depression and anxiety [26,36]. However, this is the first study that assessed PMH among individuals meeting DSM-IV criteria for AUD.…”
Section: Discussionmentioning
confidence: 58%
“…7,11 Such increases may reflect potential improvements in accuracy in young people's reporting because of greater recognition of mental health issues. 11 Alternatively, increases may represent an actual rise in difficulties. It is beyond the scope of this paper to speculate as to what might drive such a rise but many factors have been suggested including the impact of austerity, 12 increasing experience of academic pressures, 13 reduced rates of sleep 14 and increased use of social media.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a critical period for the emergence of mental disorders, 1 2 and there is evidence to suggest that adolescents are presenting to mental health services in increasing numbers, 3 with rates increasing most for those between the ages of 15 and 18 years. [4][5][6] This can be explained in part by a greater acceptability of seeking care, but also by increases in prevalence of anxiety and mood disorders. 6 At present it is estimated that under 30% of those who need mental healthcare actually access it.…”
Section: Introductionmentioning
confidence: 99%